A Study on the Issue of Orphan’s Dropping School with Reference to Mysuru District - S. , Hamsa; M., V. Raghunandan (International Journal of Psychosocial Rehabilitation, 2020)
Education status is the most vital indicator of children wellbeing and for their upcoming life opportunities. But in the case of orphans, it is completely different, where they face many challenges to continue their education. This research covers why some bereaved children drop out of school in Mysore district regardless of concerned exertions from the government of India. It mainly focuses on the factors that are influencing orphans to drop out from schooling and also to explore the lives of orphans after school dropout. The study was conducted based on a random sampling method, and primary data has been collected from respondents through a structured questionnaire. The statistical tools that are used to analyze the objectives are Chi Square and Correlation. It is found that still many orphans are facing challenges in continuing their education due to lack of motivation, poverty, disinterested in education and personal interest to earn income and it was also found that after discontinuing their education there are unable to fulfil their basic necessities. This clearly shows that there is a need for additional efforts from the government, community members, and school authorities in bringing down the dropouts’ rate.